CORTICOSTEROID RESPONSIVE COVID-19 ENCEPHALITIS - CASE REPORT - Atanasovski, Petar; Zdravkov, Ilija; Perovska, Marija; Kostova, Elena; Kostov, Hristijan (SHMSHM - AAMD, 2024)
The epidemiological burden of COVID-19 is a healthcare challenge reflected throughout the world. Different specialties are constantly confronted with unique cases that add to the array of Covid-19 symptoms. The neurological manifestations of SARS-CoV-2 infected patients are receiving increasing attention with the global spread of SARS-CoV-2. We present a novel case of SARS-CoV-2 associated acute encephalitis in a young adult without comorbidities and mild symptoms of infectious syndrome. The pathophysiological mechanism of acute encephalitis in COVID-19 is not well defined. There are two main hypotheses: a direct cytopathic effect of the infection of the brain tissue (the angiotensin-converting enzyme 2 receptors that the virus uses for attachment, margination, and internalization in the lung, are also expressed in the central nervous system; viral antigens were detected in CSF and brain samples), and an autoimmune/immunemediated cause (the general hyperinflammatory state releases cytokines and chemokines that impairs the bloodbrain barrier permeability and activate neuro-inflammatory cascades). In our case, the acute encephalitis induced by COVID-19 had a benign course, the patients improved quickly after IV steroids treatment and returned to their baseline state of health.
Keywords: COVID-19; encephalitis; SARS-CoV-2